2020
DOI: 10.1186/s13568-020-0947-6
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein 70 (HmHsp70) from Hypsizygus marmoreus confers thermotolerance to tobacco

Abstract: The 70-kD heat shock proteins (Hsp70s) have been proved to be important for stress tolerance and protein folding and unfolding in almost all organisms. However, the functions of Hsp70s in mushroom are not well understood. In the present study, a hsp70 gene from Hypsizygus marmoreus, hmhsp70, was cloned and transferred to tobacco (Nicotiana tabacum) to evaluate its function in thermotolerance. Sequence alignments and phylogenetic analysis revealed that HmHsp70 may be located in the mitochondria region. qPCR ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…In our previous report, one Hsp70 (A0A369K2K3) gene, hmHsp70, was cloned from H. marmoreus and cloned into tobacco. The transgenic tobacco showed enhanced resistance to lethal temperature (Xu et al, 2020). Similar result was observed in this study, the expression of HmHsp70 increased by 8.805 fold and then decreased to 0.747 fold after recovery cultivation.…”
Section: Proteins Related To Protein Folding and Degradationsupporting
confidence: 89%
“…In our previous report, one Hsp70 (A0A369K2K3) gene, hmHsp70, was cloned from H. marmoreus and cloned into tobacco. The transgenic tobacco showed enhanced resistance to lethal temperature (Xu et al, 2020). Similar result was observed in this study, the expression of HmHsp70 increased by 8.805 fold and then decreased to 0.747 fold after recovery cultivation.…”
Section: Proteins Related To Protein Folding and Degradationsupporting
confidence: 89%
“…In plants, it has been observed that initial exposure from medium to high heat stress provides resistance against a subsequent lethal dose. This phenomenon is called acquired tolerance [38,39]. The heat stress response is characterised by an elevated synthesis of a specific set of heat shock proteins (Hsps) associated with the development of thermotolerance [40][41][42].…”
Section: Heat Stress Modelmentioning
confidence: 99%
“…Nevertheless, the signal transduction processes and the regulation mechanism of HSPs in H. marmoreus under heat stress remain unclear. The key proteins identified by proteomics analysis have been successfully used to rebuild and enhance the thermotolerance of mushrooms (Wang et al, 2018b;Xu et al, 2020). Therefore, this study may be helpful for the breeding of heat-resistance H. marmoreus strains.…”
Section: Resultsmentioning
confidence: 95%
“…strain G12 used in this study was provided by Shandong Provincial Key Laboratory of Applied Mycology. H. marmoreus mycelia were cultivated in potato dextrose agar (PDA: extract from 200 g potato, 20 g dextrose, 20 g agar) plate at 25 • C in darkness as previously described (Wang et al, 2019;Xu et al, 2020). A total of 60 plates were divided randomly into three groups: Con group, HS group, and RHS group.…”
Section: Strains Cultivation Conditions and Heat Stress Treatmentmentioning
confidence: 99%
See 1 more Smart Citation